THE USE OF BINGO GAMES IN EFL VOCABULARY CLASS: A CASE STUDY OF INDONESIA JUNIOR HIGH SCHOOL STUDENTS - Tambunan, Resni Mawarni; Rahman, Benni Ichsanda (Universitas PGRI Sumatera Barat, 2023)
Vocabulary is an important basic skill for learning English, because it contains the basis for the development of all other skills such as reading, speaking, writing, and listening. This study aims to explain the reflections of English foreign language (EFL) learners after using the Bingo game and to explore their perceptions of it is benefits. This research uses qualitative method. The results obtained from questionnaires and interviews. This research was conducted at a private junior high school in Medan, Indonesia. Twenty six college students participated in this study (12 females 14 males). The data from the questionnaire was viewed, and the results showed that most of the students were happy with how the Bingo game helped them learn new vocabulary. It can be seen that, in the second meeting, some students participated more actively than at the first meeting. When they don't know the vocabulary they looked up the dictionary or asked the teacher. In the second meeting, the students showed more confidence when they talked in front of their classmates and all of the students participated actively during the lesson. Bingo games can increase students'' vocabulary achievement and motivation. The results of the study show that bingo games are beneficial in three aspects: improving their learning outcomes, a more enjoyable learning environment, and increasing student learning motivation. The effectiveness of the benefits of bingo games in learning vocabulary has a positive impact on the benefits felt by students.